Acute Effective of Chromiume on the Simocephalus expinosus and Mesocyclops hyalinus - Al-Doori, N.L.; Bassat, S.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of acute toxicity of chromium as (k2Cro4) on Simocephalus  expinosus (cladocera) and Mesocyclops hyalinus (cyclopoida) was studied in the present study .Both species can be used as asutible biological indecaters. In addition  Both of them are part of crustacean zooplankton.Their position in the fresh water  food chain, as the cladocerans constitutes the primary consumers while cyclopoids are part of secondary consumers.         To determine LC50 of chromium for the two species the following concentrations  of chromium  were  used 1,2, 3,4, 5,6, 14,18, 22,26,28, and 30 ppm. The results showed that LC 50 of chromium after 48 hrs. were 2.842 ppm and 23.604 ppm for  S. expinosus and  M. hyalinus respectively, which means that the sensivity to chromium is much higher in S.expinosus than in  M. hyalinus.